1997
DOI: 10.1093/rheumatology/36.10.1082
|View full text |Cite
|
Sign up to set email alerts
|

Combination of sulphasalazine and methotrexate versus the single components in early rheumatoid arthritis: a randomized, controlled, double-blind, 52 week clinical trial

Abstract: To compare the efficacy of sulphasalazine, methotrexate, and the combination of both in patients with early rheumatoid arthritis (RA), not treated with disease-modifying anti-rheumatic drugs previously, we conducted a double-blind, double-dummy, controlled, clinical trial. One hundred and five patients with active, early RA, rheumatoid factor and/or HLA DR1/4 positive were randomized between sulphasalazine (SSZ) 2000 (maximum 3000) mg daily, or methotrexate (MTX) 7.5 (maximum 15) mg weekly, or the combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(100 citation statements)
references
References 16 publications
5
85
1
9
Order By: Relevance
“…MTX, the anchor drug in RA treatment, is effective as a single agent but also serves as the basis for combination therapies with other DMARDs, such as SSZ. Initial clinical studies with the combination of MTX plus SSZ were empirically driven by the proven efficacy of both DMARDs as single agents (10,11), although a biochemical basis for the putative additive or synergistic effects of the combination was still lacking. In fact, extensive clinical evaluation of the combination of MTX plus SSZ revealed no superior activity over monotherapy with either DMARD (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTX, the anchor drug in RA treatment, is effective as a single agent but also serves as the basis for combination therapies with other DMARDs, such as SSZ. Initial clinical studies with the combination of MTX plus SSZ were empirically driven by the proven efficacy of both DMARDs as single agents (10,11), although a biochemical basis for the putative additive or synergistic effects of the combination was still lacking. In fact, extensive clinical evaluation of the combination of MTX plus SSZ revealed no superior activity over monotherapy with either DMARD (15).…”
Section: Discussionmentioning
confidence: 99%
“…RA, SSZ (2-3 gm/day) is often combined with the anchor drug methotrexate (MTX) (7.5-15 mg/week), although this combination therapy does not display additive/synergistic effects compared with monotherapy with either SSZ or MTX (10,11). In fact, addition of a third component such as hydroxychloroquine (12,13) or prednisone (14) is usually required to significantly improve clinical efficacy.…”
mentioning
confidence: 99%
“…In fact, several combination regimens involving SSZ failed to demonstrate efficacy in well-designed controlled studies that included combinations of MTX plus SSZ (27,28), as well as MTX plus azathioprine (29). Moreover, recent data have indicated that the combination of MTX and SSZ should produce little benefit, given their biologic interactions (30).…”
Section: Study Design Issuesmentioning
confidence: 99%
“…Early open-label studies showed promising results (120), but often there was increased toxicity without clear demonstration of a synergistic effect of the multiple DMARDs. However, a number of these studies either had insufficient statistical power to detect differences between treatment groups, used DMARDs that were subsequently found to be weakly active as single agents, or used suboptimum dosages (119,121,122).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%